2019
DOI: 10.1038/s41533-019-0126-x
|View full text |Cite
|
Sign up to set email alerts
|

The health and social implications of household air pollution and respiratory diseases

Abstract: Approximately three billion individuals are exposed to household air pollution (HAP) from the burning of biomass fuels worldwide. Household air pollution is responsible for 2.9 million annual deaths and causes significant health, economic and social consequences, particularly in low- and middle-income countries. Although there is biological plausibility to draw an association between HAP exposure and respiratory diseases, existing evidence is either lacking or conflicting. We abstracted systematic reviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 79 publications
0
63
2
1
Order By: Relevance
“…The respiratory system is frequently the primary target of IAP effects because pollutants often enter into the human body through inhalation. Depending on the area of the affected respiratory tract, acute respiratory infections can be classified into acute lower respiratory infections (ALRIs) and upper respiratory infections (URIs) [137]. URIs are illnesses involving the upper respiratory with common symptoms, such as cough, sinusitis, and otitis media [138], and they are often mild in nature and caused by biological pollutants (viruses, bacteria, fungi, fungal spores, and mites).…”
Section: Acute Respiratory Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respiratory system is frequently the primary target of IAP effects because pollutants often enter into the human body through inhalation. Depending on the area of the affected respiratory tract, acute respiratory infections can be classified into acute lower respiratory infections (ALRIs) and upper respiratory infections (URIs) [137]. URIs are illnesses involving the upper respiratory with common symptoms, such as cough, sinusitis, and otitis media [138], and they are often mild in nature and caused by biological pollutants (viruses, bacteria, fungi, fungal spores, and mites).…”
Section: Acute Respiratory Infectionmentioning
confidence: 99%
“…URIs are illnesses involving the upper respiratory with common symptoms, such as cough, sinusitis, and otitis media [138], and they are often mild in nature and caused by biological pollutants (viruses, bacteria, fungi, fungal spores, and mites). Meanwhile, ALRI, an acute infection of the lung, is caused by viruses or bacteria, resulting in lung inflammation [137]. It has been found that IAP increases the risk of childhood ALRI by 78%, which leads to a million deaths in children under 5 years of age every year [139].…”
Section: Acute Respiratory Infectionmentioning
confidence: 99%
“…The disease has become a silent killer in low-and middle-income countries because of its slow progression in many patients [6][7][8]. Currently estimated to affect 328 million people worldwide, COPD is expected to become one of the leading causes of death within the next 2 decades, although data from outside the USA and European Union are still limited [9][10][11]. There has been a lack of funding for COPD research compared to that provided for other causes of global mortality and morbidity, despite the major public health problem COPD poses [12].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] To evaluate the impact of outdoor air pollution on human health and implement appropriate protection policies, relevant studies have been conducted in the past decades. [ 2 , 3 ] Many adverse health problems have been reported associated with air pollution, including respiratory diseases (rhinitis, asthma, bronchitis, and pneumonia), [ 4 ] cardiovascular diseases (stroke, cardiac arrhythmias, and ischemic heart disease), [ 5 ] chronic obstructive pulmonary disease (COPD), [ 6 ] more rarely, conjunctivitis, [ 7 ] skin disease, [ 8 ] and cough. [ 9 ] Researches on the correlation between air pollution and respiratory diseases (such as asthma and COPD) are abundant, [ 6 ] while few studies investigated the correlation of allergic rhinitis (AR) with air pollution in China.…”
Section: Introductionmentioning
confidence: 99%